IMPLEMENTATION OF INDUSTRY-BASED INDEPENDENT CURRICULUM AT MUHAMMADIYAH 1 VOCATIONAL SCHOOL, SURAKARTA - Purnomo, Wahyu Ardi; Mustofa, Triono Ali (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
The rapid development of technology that affects the world of industrial technology, on this occasion we conducted research in a school in the city of Surakarta which became one of the places to prepare human resources who will later be involved in the industrial world. The purpose of this study was to find information related to the implementation of an industry-based curriculum at SMK Muhammadiyah 1 Surakarta, obstacles in the implementation of an industry-based curriculum at SMK Muhammadiyah 1 Surakarta and efforts made to overcome obstacles in the implementation of this industry-based curriculum. We collected data using a qualitative approach by conducting in-depth interviews, direct observation and documentation analysis. The results of this study are that we get information that the industry-based curriculum is implemented by establishing cooperation between the school and the industry by providing learning materials tailored to the needs of the industry, then the obstacles in implementing this curriculum are limited practical supporting infrastructure that must always be adapted to the rapid development of technology, the ability of teachers who always have to be improved to keep up with new material in accordance with technological developments, and there are some mental students who are not ready with job offers outside the area. Of the several obstacles that exist, the school also tries to overcome these obstacles by making student practice groups to optimize learning time and establishing partners with industry to participate in meeting the needs of infrastructure to support practice, teachers and the industry also always coordinate related to the material that must be adjusted to the needs of the industry, then the mentality and attitude of students who are always prepared to be ready to enter the world of work.